Evaluation of the Immunogenisity of Immune Complex Infectious Bursal Disease Vaccine Delivered In ovo to Embryonated Eggs or Subcutaneously to Day-Old Chickens - Hassanzadeh, Mohammad; Fard, Mohammad Hassan Bozorgmehri; Tooluo, Ali (International Journal of Poultry Science, 2005)
Immune complex vaccine of infectious bursal disease (IBD) were applied in ovo to embryonated eggs and subcutaneously to newly-hatched chickens in the hatchery, while the other group of chickens received a conventional IBD vaccine at days 12, 17 and 22 of age. At day 28 of age, ten chickens from each group were challenged with the field strain of IBD virus. Hatchability of eggs, survival of chicks, antibodies titres against Newcastle disease (ND) and IBD viruses were determined. Bursal index of post-challenged chickens were also measured. The present data indicates that in ovo IBD vaccination did not affect the hatchability of eggs or survival of hatched chicks. Vaccination with immune complex vaccine did not interfere with the degree of protection induced by ND vaccines. Moreover, this finding demonstrates that immune complex vaccine similar to that of conventional vaccine is able to provoke active immunity of birds and seem to protect chickens sufficiently from the IBD.